Non-take-up of rights and precariousness in the Brussels Region - Laurence Noël (Brussels Studies)
Non-take-up of rights and services is a situation in which an eligible person does not benefit from one or more rights to which he or she is entitled. The Brussels Region in particular is confronted with the problem for several fundamental social rights. Analyses of individual situations, people's pathways and legal developments have shown specificities according to the benefits. Several factors emerge: legal changes in the granting and maintenance of social rights, the increase in the number of criteria and procedures to be completed, accessibility procedures and the growing complexity and instability of status in the pathways of people in precarious situations. A significant proportion of beneficiaries are discouraged and some professionals no longer feel able to verify or assert eligibility due to the growing complexity. Finally, the high level of digitalisation of services (public and private) prior to the pandemic which has accelerated since the first lockdown, reinforces the risk of non-take-up while there is a growing need for concrete, human help and simplification, as well as a deterioration of trust between citizens and the state.